Implementasi Kebijakan Actip di Indonesia: Studi Kasus Kantor Imigrasi Bandara Soekarno Hatta Periode 2023-2024 - Shafira Kezia Andjani; Hartanto Hartanto (Student Scientific Creativity Journal, 2026)
Human trafficking is a transnational crime involving multiple countries and remains a serious challenge for Indonesia. As an ASEAN member state, Indonesia has adopted the ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP) through Law Number 12 of 2017 as a foundation for regional cooperation in preventing and combating the Crime of Human Trafficking (TPPO). This study aims to analyze the implementation of the Prevention aspect of ACTIP at the Class I Immigration Office Special for Inspection (TPI) at Soekarno-Hatta Airport during 2023–2024 by applying Stephen D. Krasner’s International Regime Theory. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews with three informants from the Soekarno-Hatta Airport Immigration Office and document analysis of regulations, official reports, and relevant literature. The findings reveal that ACTIP’s Prevention aspect has shifted from administrative inspection toward risk-based border management through the use of immigration technologies, including SIPP, BCM, Autogate, and the SOI Database. These practices indicate the integration of ACTIP norms through institutional strengthening, technological utilization, and inter-agency coordination. However, challenges remain, particularly in implementing awareness campaigns and addressing the limitations of the ASEAN Way. The study concludes that ACTIP effectiveness depends on both regional legal frameworks and the capacity of member states to internalize international regime norms into domestic policies and practices.